Persistent self‐reported ear and hearing problems among World Trade Center‐exposed firefighters and emergency medical service workers, 2001‐2017—A longitudinal cohort analysis. Issue 1 (6th December 2018) - Colbeth, Hilary L.; Zeig‐Owens, Rachel; Liu, Yang; Webber, Mayris P.; Schwartz, Theresa M.; Hall, Charles B.; Prezant, David J.
Abstract : Background: The goal of this study was to estimate the impact of exposure to the World Trade Center (WTC) site on annual and persistent rates of otalgia and hearing impairment among Fire Department of the City of New York (FDNY) Firefighters and Emergency Medical Service Workers (EMS). Methods: Responders completed routine physical health questionnaires at monitoring visits. We used logistic and marginal logistic regression models to explore the association between otalgia and hearing impairment and WTC arrival time. Results: The highest‐exposed group had greater odds of persistent ear symptoms (OR 1.33, 95%CI 1.11‐1.59) compared with the least‐exposed; the odds of persistent hearing problems between the groups were not significantly different. We found consistent WTC‐exposure gradients when the average population odds of these outcomes were assessed each year. Conclusions: Our findings demonstrate that the odds of long‐term ear symptoms were significantly associated with the intensity of WTC exposure.